The Meaning of Tri Tangtu Value in Sundanese Traditional Game “Oray-orayan” - Erna Nurmalinda (Universitas Pasundan, 2021)
Abstract In West Java (Bandung) there are copious traditional games that are actually still played by children. But because of technological advances and the absence of fields for playing, the traditional games is now sidelined and even forgotten. Games are offered now, not only traditional games but also the games that sophisticated technological based derived from abroad. The traditional games of West Java that used to be played have been put aside. Traditional “Oray-orayan” game is a game of boys and girls known since ancient times. Besides educational elements (choir, sports and sensitivity) this game is also containing a fun entertainment for children. In Traditional Games “Oray-orayan” the desires can arise from thoughts or deeds, then the mind or knowledge evokes desire, after that there is a process of thought so that desire can manifested in action. The pattern of the three relationships in Tritangtu can be known from the structure of objects or artifacts. Tritangtu reflects and is represented in all systems and sub systems in Sundanese culture such as the State system, Social system, Legal system, Art system and others that relates to Tritangtu principles. Keywords; Game, Traditional, Oray-orayan, Meaning, Tritangtu